Il fornaretto di Venezia tra letteratura e cinema - Radi, Sonia (Acta Histriae, 2007)
The story of the little baker from Venice, Pietro Tasca, was born at the end of the 18th century. The legend is centred on the calamitous judicial error made by the magistracy of the Council of Ten at the beginning of the 16th century that resulted in Pietro's sentence to death. The legend was created in order to transmit a vision of justice that is always in search for the truth and that - in order to achieve this goal - does not hesitate to publicly admit the error that caused the death of the little baker. The greatness of the Venetian government that does not fear to admit having committed a huge mistake has thus become an emblem of the myth of the Republic of Venice
Keywords: 18.st.; Beneška republika; legende; Republic of Venice; sodbe; sodne napake